ONE WEEK THERAPY WITH ORAL TERBINAFINE IN CASES OF TINEA CRURIS/CORPORIS - Khan, Imranullah; Javed, Muhammad; Shah, Humayun (Journal of Ayub Medical College Abbottabad, 1996)
We conducted a study on 27 patients (17 males, 10 females) to evaluate the efficacy of oral Terbinafine on a short term basis. All the patients had clinical and mycologically proven tinea cruris I corporis. Each patient was given 250 mg Terbinafine (Lamisil) after meals, once daily for one week. Patients were followed up for 6 weeks after completion of treatment. Patients were assessed clinically and mycologically at the end of treatment and the end of the follow up period. The signs and symptoms of the disease had almost disappeared at the end of the follow up period. Mycological investigations were negative in all patients at this time, except for one. As reported in other studies, our results show that one-week oral therapy with 250 mg/day of Terbinafine is effective and cheap for the treatment of tinea corporis/cruris